The Attribution Theory Of As a Psycho-Social Approach to thePerception of Occupational Health and Safety: A Focus GroupStudy Among Women Workers in Metal Industry - Aytac, Serpil; Akalp, Gizem (European Journal of Multidisciplinary Studies, 2022)
Nowadays, women involved in working life with the industrial revolution provide their labor as much as men and are affected by the risk factors in the workplace as much as men. Women are more affected by the psycho-social risk factors because of gender roles and they are also more affect society because of important central role in the family. Psycho-social risks that is one of the occupational health and safety risk factors affect employee attitude and performance to work at least as much as the other risk factors. In this study, researchers aim that reveal awareness’s about psychosocial risk factors in their workplace in metal industries in Turkey. In addition, negative attitudes of workers about occupational health and safety practices will be examined with attribution theories in social psychology. In this study, we used qualitative method. Data were collected with focus group study at eight different groups in two different days from woman member of Turkish Metal Union in Bursa city in Turkey. Totally 155 employees participated in the focus groups study. Job satisfaction, job stress, wellness, the relationship with coworkers and managers were evaluated in this study. This study was supported and funded (Project USIP (?) 2014/7) by the Scientific Research Projects Commission of Uludag University cooperated with Turkish Metal Union. According to the obtained results, work stress emerges as an important psychosocial risk factor. In addition to, stress and lack of communication are important factors causing job dissatisfaction.